2009
DOI: 10.1111/j.1365-2486.2009.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of terrestrial biogeochemistry in coupled climate–carbon models

Abstract: With representation of the global carbon cycle becoming increasingly complex in climate models, it is important to develop ways to quantitatively evaluate model performance against in situ and remote sensing observations. Here we present a systematic framework, the Carbon‐LAnd Model Intercomparison Project (C‐LAMP), for assessing terrestrial biogeochemistry models coupled to climate models using observations that span a wide range of temporal and spatial scales. As an example of the value of such comparisons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
300
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 93 publications
7
300
0
Order By: Relevance
“…Although an earlier version of CLM-CN had an attenuated seasonal cycle of atmospheric CO 2 across the northern hemisphere (19), introduction of a photoperiod correction on V cmax reduced bias and mean absolute error for seasonal cycle amplitude by 49% and 34%, respectively (mean of 60 stations globally) (Fig. 4 and Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an earlier version of CLM-CN had an attenuated seasonal cycle of atmospheric CO 2 across the northern hemisphere (19), introduction of a photoperiod correction on V cmax reduced bias and mean absolute error for seasonal cycle amplitude by 49% and 34%, respectively (mean of 60 stations globally) (Fig. 4 and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…As an evaluation of introducing a day-length correction on a broadly integrative global-scale metric, we gauged model performance with and without a simple photoperiod control for 1988-2004 to assess the amplitude and phase of seasonal cycles of atmospheric CO 2 concentration, using the C-LAMP protocol and metrics (19), adding observations from the southern hemisphere. Although an earlier version of CLM-CN had an attenuated seasonal cycle of atmospheric CO 2 across the northern hemisphere (19), introduction of a photoperiod correction on V cmax reduced bias and mean absolute error for seasonal cycle amplitude by 49% and 34%, respectively (mean of 60 stations globally) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a starting point, Stö ckli et al (2008) and Randerson et al (2009) have emphasized the importance of developing better data sets with which to test and evaluate model predictions. Comparative analyses of different phenological models have typically used data from only a single site (e.g., Richardson & O'Keefe, 2009), which hinders the development and parameterization of generalized models.…”
Section: Data Needsmentioning
confidence: 99%
“…They concluded that model bias toward under-predicting temperate and boreal forest uptake of CO 2 could be attributed to a 1-3 month delay in predicting the timing of maximum LAI in these ecosystems, compared to estimates derived from MODIS data. Randerson et al (2009) also noted that the two models they evaluated tended to predict a longer growing season than was actually observed in temperate ecosystems, with photosynthetic uptake occurring too early in the spring and too late in the autumn, compared with ground observations. Errors in LAI would likely propagate to errors in partitioning the available energy to latent and sensible heat fluxes, and errors in the timing of photosynthetic uptake would also affect the seasonality of modeled atmospheric CO 2 concentrations, emphasizing the importance of accurate representation of phenologically mediated processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation